HUBUNGAN PERSEPSI KECUKUPAN SUPLAI ASI DAN PRAKTIK PEMBERIAN ASI EKSKLUSIF: ASESMEN DENGAN THE HILL AND HUMENICK LACTATION SCALE DI DAERAH SUBURBAN - Lila Kartika, Maudy; Arta Puspitasari, Nike; Pramesti, Raissa (Jurnal Ilmu Psikologi dan Kesehatan (SIKONTAN), 2026)
Mothers’ perception of breast milk supply adequacy is an important determinant of exclusive breastfeeding success. Negative perceptions of insufficient milk production may reduce maternal confidence and increase the likelihood of introducing complementary foods before six months. The Hill and Humenick Lactation Scale (HHLS) is a validated instrument that comprehensively measures mothers’ perceptions of breast milk supply adequacy. This study aimed to examine the association between perceived breast milk supply adequacy based on the HHLS and exclusive breastfeeding practices among breastfeeding mothers in suburban communities. A cross-sectional study was conducted at RBC Holis Clinic involving 75 breastfeeding mothers with infants aged 0–6 months selected through incidental sampling. Data were collected using a translated and validated HHLS questionnaire. The association between variables was analyzed using the chi-square test with a significance level of p < 0.05. Most respondents reported positive perceptions of breast milk supply adequacy. Statistical analysis revealed a significant association between perceived milk supply adequacy and exclusive breastfeeding practices (p < 0.05). Mothers with positive perceptions were more likely to exclusively breastfeed than those with negative perceptions. These findings indicate that maternal perception of breast milk supply is closely associated with exclusive breastfeeding. Strengthening perception-based education and lactation counseling may improve exclusive breastfeeding outcomes in suburban communities.